Modulation of cyclic AMP metabolism by S-adenosylhomocysteine and S-3-deazaadenosylhomocysteine in mouse lymphocytes. - Zimmerman, T P (1980)
Mouse lymphocytes incubated with micromolar concentrations of adenosine or 3-deazaadenosine, in medium supplemented with L-homocysteine, rapidly accumulated supramillimolar concentrations of S-adenosylhomocysteine (AdoHcy) or S-3-deazaadenosylhomocysteine (c3AdoHcy), respectively. Lymphocytes thus preloaded with high levels of AdoHcy or c3AdoHcy exhibited markedly enhanced (5- to 40-fold) cyclic AMP responses to prostaglandin E1, adenosine, 2-chloroadenosine, isoproterenol, and cholera toxin. This enhancement of cyclic AMP response by intracellular AdoHcy or c3AdoHcy was attributable both to amplification of the activity of adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] and to inhibition of cyclic AMP phosphodiesterase (3',5'-cyclic-nucleotide 5'-nucleotidohydrolase, EC 3.1.4.17). Basal and prostaglandin E1- and isoproterenol-stimulated activities of adenylate cyclase, assayed in lymphocyte homogenates, were increased 1.3- to 2.0-fold after treatment of the cells with homocysteine plus either adenosine or 3-deazaadenosine. AdoHcy and c3AdoHcy were found to be competitive inhibitors (with Ki values of 1.7 and 4.8 mM, respectively) of the high-affinity cyclic AMP phosphodiesterase present in lymphocyte homogenates. It is evident, therefore, that increased cellular levels of AdoHcy or c3AdoHcy can affect cellular physiology via perturbation of cyclic AMP metabolism as well as via inhibition of S-adenosylmethionine-dependent methylation reactions.